Bad Kitty : camp Daze - Bruel, Nick (New York : Roaring Book Press, 2019)
"Kitty's life is really hard. Like really, REALLY hard. All she asks for is twenty-two hours a day to sleep and food to be delivered morning and night. But does she get it? No. And when Puppy and Baby get a little rambunctious during her naptime, Kitty gets bonked on the head and starts to believe she's ... a dog."--Publisher's description.
"A Neal Porter Book."
Keywords: Bad Kitty -- (Fictitious character from Nick Bruel) -- Juvenile fiction; Camping -- Juvenile fiction; Cats -- Juvenile fiction; Dogs -- Juvenile fiction; Humorous stories; Graphic novels; Graphic novels